Research on the Simulation Design of Humanistic Landscape Optimization in Urban Residential Area Based on Computer Technology (Informatica, 2019)
Abstract: With the development of social material and the civilization of human society, people are paying more attention to their own living environment. They attach great importance to the harmony between the urban layout and the overall natural environment, and pursue a simple and comfortable living style. This paper first expounds the concept of residential area and landscape planning, the basic principles of residential landscape planning and other relevant theoretical knowledge. Then the concrete planning and design of the urban residential landscape are carried out from different layers. The author puts forward a model of optimization design of humanistic landscape in urban residential area based on computer technology. The simulation results show that the improved method provides a theoretical basis for the future urban landscape design. Key words:computer technology; urban residential area; humanistic landscape